## Solving the Equation: (x+3) + 2(x+3) = 3

This article will walk you through the steps of solving the equation (x+3) + 2(x+3) = 3. We'll use the principles of algebra to isolate the variable 'x' and find its value.

### Step 1: Distribute

First, we distribute the 2 in front of the second parenthesis:

(x+3) + 2(x+3) = 3 x + 3 + 2x + 6 = 3

### Step 2: Combine Like Terms

Next, we combine the 'x' terms and the constant terms:

x + 2x + 3 + 6 = 3 3x + 9 = 3

### Step 3: Isolate the Variable

To isolate the 'x' term, we subtract 9 from both sides of the equation:

3x + 9 - 9 = 3 - 9 3x = -6

### Step 4: Solve for 'x'

Finally, we divide both sides of the equation by 3 to solve for 'x':

(3x) / 3 = (-6) / 3 x = -2

### Conclusion

Therefore, the solution to the equation (x+3) + 2(x+3) = 3 is **x = -2**.